2016
DOI: 10.1016/j.ygcen.2015.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and significance of corticosterone regulation in the songbird brain

Abstract: Songbirds exhibit significant adult neuroplasticity that, together with other neural specializations, makes them an important model system for neurobiological studies. A large body of work also points to the songbird brain as a significant target of steroid hormones, including corticosterone (CORT), the primary avian glucocorticoid. Whereas CORT positively signals the brain for many functions, excess CORT may interfere with natural neuroplasticity. Consequently, mechanisms may exist to locally regulate CORT le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 120 publications
(137 reference statements)
0
6
0
Order By: Relevance
“…In free-living birds, corticosterone may be involved in delaying the onset of breeding including via altering hormone titers, negative feedback regulation, plasma binding globulin concentrations, intracellular receptor concentrations, enzyme activity and interacting hormone systems [193]. It is also implicated in corticosterone regulation in the songbird brain [194]. Such diverse functions may indeed be facilitated via post-translational changes, including deimination recognised here.…”
Section: Discussionmentioning
confidence: 89%
“…In free-living birds, corticosterone may be involved in delaying the onset of breeding including via altering hormone titers, negative feedback regulation, plasma binding globulin concentrations, intracellular receptor concentrations, enzyme activity and interacting hormone systems [193]. It is also implicated in corticosterone regulation in the songbird brain [194]. Such diverse functions may indeed be facilitated via post-translational changes, including deimination recognised here.…”
Section: Discussionmentioning
confidence: 89%
“…This study tested the hypothesis that the enzymes 11β-HSD1 and 11β-HSD2 are expressed in regions of the adult zebra finch brain with elevated sensitivity to GCs. Whereas widespread changes in GC exposure can be initiated by regulation of adrenal synthesis, secretion, and association with binding globulins, local regeneration and metabolism of GCs, respectively, may enable regions requiring precise GC regulation to control access to receptors on a fine scale ( 8 ). Our results in the finch vary significantly from expression patterns reported in rodents ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, while CBGs are thought to prevent access to target tissues ( 77 ), some studies suggest that CBGs are actually necessary for GC delivery to the brain, making any conclusions preliminary at this time ( 78 ). In the end, a vital difference between the brains of rodents and songbirds remains the widespread neuroplasticity that persists into adulthood in the songbird brain and which is present to a much smaller degree in rodents ( 8 ). Given the capacity for GCs to influence such plasticity, it seems likely that the expression of CORT metabolic enzymes in the adult avian brain is related to this inherent neuroplasticity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that isolation stress had the greatest impact on the metabolome of the hippocampus of broiler chicks. In contrast, the metabolome of the hippocampus was not particularly affected by either heat or corticosterone-incited stress, even though corticosterone is able to cross the chickens’ blood–brain barrier [ 119 ]. Under certain stress conditions, the hippocampus in birds is protected from incoming corticosterone, and although the mechanisms behind this are currently unknown [ 119 ], it is likely that protection is mediated by corticosteroid-binding globulins in the brain [ 120 , 121 , 122 , 123 ].…”
Section: Discussionmentioning
confidence: 99%